Fractionated Radiation Therapy for Large and Giant Cavernous Sinus Hemangioma: A Retrospective Study - Xin, Zengfeng; Yao, Yihan; Chen, Guodi; Wang, Liancong; Shu, Meibao; Lv, Qinghua; Yu, Haifeng; Zhang, Ting (Frontiers in Neurology, 2020)
Purpose: Surgical resection has been traditionally used as a treatment for cavernous sinus hemangioma (CSH). However, this is usually difficult due to tumor vascularity and results in complications especially in large and giant CSH (volume >20 cm3). Previous studies have reported that radiotherapy (RT) provides an alternative treatment modality for hemangiomas. However, the optimized dose and fractions which control CSH and also protect the cognitive function remain unclear. This study reports our experience in the management of symptomatic large and giant CSH. Methods: Fifty-four patients with symptomatic large (20 cm3tumor volume40 cm3, 3-4 cm in diameter) and giant (tumor volume40 cm3, 4 cm in diameter) CSH were enrolled in a retrospective study between January 2007 and December 2018. The prescription dose to the target margin was 50 Gy in 25 fractions. Results: The mean pre-RT tumor volume was 60.9 cm3 which ranged from 20.2 to 230.5 cm3. The clinical data obtained was analyzed retrospectively following a mean follow-up period of 35.0 months which ranged from 1 to 140 months. All patients experienced tumor shrinkage within 3 months after radiotherapy. There was an average mean tumor reduction of 79.7% (range, 48.4%-98.5%) with no patients experiencing tumor progression and recurrence. All the 54 patients experienced symptomatic improvement within 1 month to 12 months after radiotherapy. Within the entire follow up period, no patients experienced any form of permanent complications or symptomatic radiation toxicity. Neurocognitive impairment studies were conducted before and after radiotherapy on 28 patients while the studies were conducted after the last follow up in 40 patients. The cognitive function of all the participants had normal MoCA-scores of 28.25 pre-radiotherapy. The post-treatment MoCA-scores were also clinically stable (28.04, p=0.78), and the average MoCA-score did not show any decline until the last follow-up (27.61, p=0.13). Conclusion: The optimal dose and fractions of radiotherapy treatment for symptomatic large and giant cavernous sinus hemangioma remain unclear. This study, therefore, used a marginal dose of 50 Gy in 25 fractions in radiotherapy and this was proven to be effective and safe in the treatment of symptomatic large and giant CSHs.